The generative dance of design inquiry: Exploring Dewey's pragmatism for design research. (November 2022) - Stompff, Guido; van Bruinessen, Ties; Smulders, Frido
Abstract : In design research, the activities of design and research coalesce. It introduces thorny epistemological challenges and Dewey's pattern of inquiry is explored for its relevance for design research. First, a logical framework for design inquiry is developed that enables to reach warranted conclusions, retrospectively. Second, a temporal framework of activities is inferred, based on the experiences of two PhD candidates. These frameworks offer guidance to (1) develop transferable knowledge; (2) by oscillating between known theories and uncharted practices until new ideas arise; whereby (3) the value of these ideas is validated through experiments (action validity); and (4) with a community of inquiry (consensual validity). The knowledge produced stems from practice, is tested in practice and serves others in future inquiries. Highlights: Dewey's pattern of inquiry is explored for its relevance for design research. A logical framework is developed that allows to reach justified transferable conclusions, but only retrospectively. A temporal framework of activities is developed, describing an iterative process of sensemaking, designing and experimenting. Design inquiry is radically practice-led and bridges the practice-theory divide.